Pengaruh Green Product dan Persepsi Harga terhadap Minat Beli Produk Tupperware - Edi Nurtjahjadi; Feby Budianti (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: To examine the impact of green product and perceived price toward purchase intention is the aim of this study. Research methodology: This study uses a quantitative approach with survey methods and questionnaire. Multiple regression analysis were used as data analysis techniques with tools SPSS version 20. Results: Of the two proposed research hypotheses, one of them has been supported by empirical data. The research findings show that perceived price effects customers' purchase intention while green products doesn't. Limitations: Ninety people has been declared as the objects observed in this research and the research locus is only in Bandung. Contribution: The use of other concepts to directly influence purchase intention can be proposed by further researchers. The results of this study also benefit Tupperware company regarding its strategy-assembling process so it is more relevant and in line with the raise in attribute qualities. Novelty: Testing the effect of green products on buying interest with objects of people who have never used Tupperware, the majority of which are students and research locus in Bandung.